Peasant Women Empowerment as a Conflict Resolution Strategy in Sidomulyo Hamlet, Baluran National Park - Dede Aprylasari; Siti Azizah; Norsida Man; Suprih Bambang Siswijono; Irfan H. Djunaidi; Anif Mukaromah Wati; Achadiah Rachmawati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The aims of this study are to 1) determine the causes of conflict between the Sidomulyo hamlet community and the Baluran National Park management; 2) find opportunities for conflict resolution through empowering peasant women. This research was carried out from April to June 2022. The method used is descriptive qualitative by direct field survey and interviews with Baluran National Park managements and Sidomulyo Hamlet farmers. Key informants were chosen using the purposive sampling method followed by snowball sampling. The data required includes the dynamics of conflict, the variety of conflicts, conflict actors, sources of conflict, and opportunities to empower women farmers. Based on the research data on the sources of conflict between the Sidomulyo community and the management of Baluran National Park, there are four different sources of conflict: differences in perceptions, knowledge, values, and values and differences in interests. Three resolutions are applied: Peacekeeping, Peacemaking, and Peacebuilding. In the Peacebuilding resolution empowerment programs is chosen because there is a big potential in for women to do entrepreneur activities. Women farmer empowerment can be done through entrepreneuship. The conservation village model through micro-credit assistance and the formation of women's farmer groups. The aim is to increase livestock yield products and the economy, income, and food security.